The interplay of ferroptosis and oxidative stress in the pathogenesis of aortic dissection - Zhaoshan Zhang; Zhaoshan Zhang; Zhaoshan Zhang; Haichao Wang; Haichao Wang; Haichao Wang; Xi Kan; Xi Kan; Xi Kan; Xiaozhao Zhang; Xiaozhao Zhang; Xiaozhao Zhang; et al. (Frontiers in Pharmacology)
Aortic dissection (AD) is a life-threatening vascular condition marked by the separation or tearing of the aortic media. Ferroptosis, a form of iron-dependent programmed cell death, occurs alongside lipid peroxidation and the accumulation of reactive oxygen species (ROS). The relationship between ferroptosis and AD lies in its damaging effect on vascular cells. In AD, ferroptosis worsens the damage to vascular smooth muscle cells (VSMCs) and endothelial cells (ECs), thereby weakening the vascular wall’s structural integrity and accelerating the onset and progression of the condition. However, the molecular mechanisms through which ferroptosis regulates the onset and progression of AD remain poorly understood. This article explores the relationship between ferroptosis and AD.